Desarrollo de una Interfaz de Usuario para una Máquina de Hemodiálisis - Olmos, K.; Gómez, M.; Rascón, L. (Cultura Científica y Tecnológica, 2015)
Desarrollo de una Interfaz de Usuario para una Máquina de Hemodiálisis